2020
DOI: 10.3390/cells9051069
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-Dependent Dynamics of the Golgi-Centrosome Association in Motile Cells

Abstract: Here, we characterize spatial distribution of the Golgi complex in human cells. In contrast to the prevailing view that the Golgi compactly surrounds the centrosome throughout interphase, we observe characteristic differences in the morphology of Golgi ribbons and their association with the centrosome during various periods of the cell cycle. The compact Golgi complex is typical in G1; during S-phase, Golgi ribbons lose their association with the centrosome and extend along the nuclear envelope to largely enci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Analysis of nuclear and Golgi size and position suggested that this increase was likely due to both nuclear and Golgi compaction combined with increased Golgi-nucleus distance, which were similar across all shear stress modalities. Based on reports of compact organellar morphologies in G1-phase hTert-RPE1 cells 56 and reports that flow leads to cell cycle arrest at G1/S transition in HUVECs 57 , we speculate that increased polarization reflects flow-mediated cell cycle arrest.…”
Section: Discussionmentioning
confidence: 67%
“…Analysis of nuclear and Golgi size and position suggested that this increase was likely due to both nuclear and Golgi compaction combined with increased Golgi-nucleus distance, which were similar across all shear stress modalities. Based on reports of compact organellar morphologies in G1-phase hTert-RPE1 cells 56 and reports that flow leads to cell cycle arrest at G1/S transition in HUVECs 57 , we speculate that increased polarization reflects flow-mediated cell cycle arrest.…”
Section: Discussionmentioning
confidence: 67%
“…As the GC is closely associated with the CEs, a possibility is that Golgi unlinking could be necessary to remove a steric hindrance that could hamper CE separation in G2. However, this is unlikely since the GC is dissociated from the CE during this phase (Frye et al, 2020). Moreover, inhibition of Golgi unlinking does not alter CEs separation (Persico et al, 2010).…”
Section: Why Is Golgi Unlinking Required For Entry Into Mitosis?mentioning
confidence: 96%
“…However, CEP250 KO cells showed defects in the spatial organization of the Golgi apparatus and cell migration [ 33 , 39 ]. It is long known that centrosome derived MTs position the Golgi apparatus of a cell [ 40 , 41 ] and therefore it is easy to envision that the two separated centrosomes in CEP250 KO cells each position spatially distinct Golgi stacks. In addition, in human and rodent cell lines, centrosome orientation was shown to be important to maintain polarization in migrating cells [ 42 , 43 ].…”
Section: Molecular Mechanisms Of Centrosome Cohesionmentioning
confidence: 99%